помогите пожалуйста не могу никак сделать!!!7 класс!

№1 Докажите тождество (b-c)(b+c)^2+(c-a)(c+a)^2+(a-b)(a+b)^2= -(a-b)(b-c)(c-a)

№2 Разложите многочлен на множители. (x-2y)^3 + (x+2y)^3

1

Ответы и объяснения

2013-04-25T19:25:11+00:00

№1

(b-c)(b+c)^2+(c-a)(c+a)^2+(a-b)(a+b)^2=-(a-b)(b-c)(c-a)
(b-c)*(b^2+2*b*c+c^2)+(c-a)*(c+a)^2+(a-b)*(a+b)^2+(a-b)*(b-c)*(c-a)=0

b^3+b^2*c-b*c^2-c^3+(c-a)*(c+a)^2+(a-b)*(a+b)^2+(a-b)*(b-c)*(c-a)=0

b^3+b^2*c-b*c^2-c^3+(c-a)*(c^2+2*c*a+a^2)+(a-b)*(a+b)^2+(a-b)*(b-c)*(c-a)=0

b^3+b^2*c-b*c^2-c^3+c^3+c^2*a-c*a^2-a^3+(a-b)*(a+b)^2+(a-b)*(b-c)*(c-a)=0

b^3+b^2*c-b*c^2+c^2*a-c*a^2-a^3+(a-b)*(a+b)^2+(a-b)*(b-c)*(c-a)=0

b^3+b^2*c-b*c^2+c^2*a-c*a^2-a^3+(a-b)*(a^2+2*a*b+b^2)+(a-b)*(b-c)*(c-a)=0

b^3+b^2*c-b*c^2+c^2*a-c*a^2-a^3+a^3+a^2*b-a*b^2-b^3+(a-b)*(b-c)*(c-a)=0

b^3+b^2*c-b*c^2+c^2*a-c*a^2+a^2*b-a*b^2-b^3+(a-b)*(b-c)*(c-a)=0

b^2*c-b*c^2+c^2*a-c*a^2+a^2*b-a*b^2+(a-b)*(b-c)*(c-a)=0

b^2*c-b*c^2+c^2*a-c*a^2+a^2*b-a*b^2+(a*b-a*c-b^2+b*c)*(c-a)=0

b^2*c-b*c^2+c^2*a-c*a^2+a^2*b-a*b^2+(-a^2*b-a*c^2+a^2*c-b^2*c+b^2*a+b*c^2)=0

b^2*c-b*c^2+c^2*a-c*a^2+a^2*b-a*b^2-a^2*b-a*c^2+a^2*c-b^2*c+b^2*a+b*c^2=0

b^2*c-b*c^2+c^2*a-c*a^2-a*b^2-a*c^2+a^2*c-b^2*c+b^2*a+b*c^2=0

b^2*c-b*c^2-c*a^2-a*b^2+a^2*c-b^2*c+b^2*a+b*c^2=0

b^2*c-b*c^2-a*b^2-b^2*c+b^2*a+b*c^2=0

-b*c^2-a*b^2+b^2*a+b*c^2=0

-b*c^2+b*c^2=0

0=0

Тождество доказано! 


№2 
(x-2y)^3+(x+2y)^3=x^3-6*x^2*y+12*x*y^2-8*y^3+(x+2*y)^3=x^3-6*x^2*y+12*x*y^2-8*y^3+x^3+6*x^2*y+12*x*y^2+8*y^3=2*x^3-6*x^2*y+12*x*y^2-8*y^3+6*x^2*y+12*x*y^2+8*y^3=2*x^3+12*x*y^2-8*y^3+12*x*y^2+8*y^3=2*x^3+24*x*y^2-8*y^3+8*y^3=2*x^3+24*x*y^2